PP.02.12: CARDIOVASCULAR RISK FACTORS IN PATIENTS HOSPITALIZED IN AN INTERNAL MEDICINE WARD. (June 2015) - Martins, R. Tourais; Pinto, B.; Santos, M.
Abstract : Objective: Cardiovascular disease is a major cause of mortality and morbidity in Portugal, so it is important to know the prevalence of cardiovascular risk factors (CRF) to be able to optimize prevention and monitoring strategies. The aim of the study was to characterize in terms of cardiovascular risk factors a sample of patients hospitalized in an Internal Medicine ward of a Portuguese regional hospital. Design and method: We performed a retrospective study of a sample of patients hospitalized in an Internal Medicine ward of a Portuguese regional hospital from May to October 2014. We analyzed anthropometric variables and cardiovascular risk factors (Hypertension, Diabetes mellitus, Dyslipidemia, Smoking, Physical inactivity and Obesity). Results: The total number of patients evaluated was 181 for a total of 195 admissions. 51% of patients were women, 153 (84.5%) were aged less than 65 years and the median age was 78 years. The average hospital stay was 9 days (adjusted mean - 7.2 days). The mortality rate was 10.3%. The main hospitalization causes were neurological conditions (20.5%), including stroke, respiratory disease (19.0%), urinary disease (17.8%) and cardiovascular disease (9.7%). Regarding CRF, there was a total of 133 (73.5%) patients with hypertension (HTA), 62 (34.3%) patients with diabetes mellitus, 59 (32.6%) patients with dyslipidemia and 17 (9.4%) patients with active smoking. 47 (26.0%) patients were overweight, 28 (15.5%) patients had class I obesity, 6 (3.3%) had class II obesity and morbid obesity. It was not possible to assess the prevalence of physical inactivity since that information was usually not included in the discharge report. The prevalence of hypertension was higher in patients aged over 65 years. Conclusions: The results confirm the high prevalence of cardiovascular risk factors, including hypertension, in patients admitted to a medical ward, even though they do not always constitute or directly relate to the main reason for hospitalization. We emphasize once again the need to know our patients as a whole and take advantage of every opportunity for prevention and control of vascular risk, including at the moment of hospital discharge.